ANALISIS BAURAN PEMASARAN PADA PT. GLOBAL IMOO TELEKOMUNIKASI BENGKULU - Suwarni Suwarni; Lusi Aprika; Nia Indriasari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
Suwarni, Lusi Aprika, Nia Indriasari; The purpose of this study was to figure out the mixed analysis of the marketing of Imoo watch phone at PT. Global Imoo Telekomunikasi Bengkulu. The sample in this study was 49 consumers who made the smart phone watches purchases at PT. Global Imoo Telekomunikasi Bengkulu. Sampling is done by accidental sampling technique. Data collection method was done using questionnaires and analytical methods which employed rating scale analysis. The results of this study indicate that the average value of respondents' responses to the marketing at PT. Global Imoo Telekomunikasi Bengkulu is 1,003 with the agreed assessment criteria. This means that the respondent has an agreed assessment of the marketing at PT. Global Imoo Telekomunikasi Bengkulu that is influenced by product, price, promotion and distribution factors. The highest factor influences the marketing mix at PT. Bengkulu Global Imoo Telekomunikasi is a product factor with a score of 1,067. This illustrates that the quality of Imoo smart phone watches products sold by PT. Global Imoo Telekomunikasi Bengkulu has good quality, besides it can be used to communicate. Furthermore, Imoo smart phone watches can also be used to monitor the whereabouts of children. The lowest factor is the price factor with a total score of 964 with agreed assessment criteria. This illustrates that the price factor has a low influence on the marketing at PT. Global Imoo Telekomunikasi Bengkulu because the price offered by Imoo smart phone watches is relatively high, compared to many smart phone watches from other brands that are sold at much cheaper prices Keywords; Product, Price, Distribution, Promotion